An Analysis of Parenting Strategies for Children with Speech Delay - Maria Yasinta Fengi; Marsianus Meka; Gde Putu Arya Oka; Elisabeth Tantiana Ngura (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The urgency of this study lies in the importance of the role of parents in providing appropriate stimulation, support, and communication to optimize early childhood language development. This study aims to describe parenting strategies in assisting children experiencing speech delay. The research employs a qualitative method with a case study approach. The research subjects include parents and teachers selected through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The results show that children experience articulation difficulties, speak in a low voice, and tend to use nonverbal communication due to limited verbal interaction and excessive mobile phone use. The strategies implemented include pronunciation correction, habituation of daily communication, utilization of visual media, and storytelling activities. This study contributes as a reference for parents and educators in applying language stimulation for children.